Pemberdayaan dan Pendampingan Anak Terlantar di Panji Berbakat Anak di Kelurahan Baru Ulu Balikpapan - Budha Maryanti; A. Asni B (Abdimas Universal, 2019)
In some corners of the city, it is often found abandoned children who roam around school hours and engage in less productive activities that disturb the peace of the community. which makes them fall into drugs. This should be a concern of the community starting from the household to the city government. In Balikpapan, specifically the "Kelurahan Baru Ulu" area which is an old and densely populated city with a very dense housing complex, this area is also called the drug-prone zone. Through this community service program can provide solutions for the care of neglected children through appropriate support and learning systems for abandoned children in "Shelter Houses" and PKBM (Community Learning Centers), using non-formal education systems in accordance with established standards called " Rumah Singgah Peduli Anak Penerus Bangsa ". This activity has been carried out and will continue to be carried out and become a reference in the shelter management activities.